2011
DOI: 10.1242/jcs.086751
|View full text |Cite
|
Sign up to set email alerts
|

A new regulatory function of the region proximal to the RGG box in the Fragile X mental retardation protein

Abstract: SummaryFragile X mental retardation protein (FMRP) is required for normal cognition. FMRP has two autosomal paralogs, which although similar to FMRP, cannot compensate for the loss of FMRP expression in brain. The arginine-and glycine-rich region of FMRP (the RGG box) is unique; it is the high-affinity RNA-binding motif in FMRP and is encoded by exon 15. Alternative splicing occurs in the 59 end of exon 15, which is predicted to affect the structure of the distally encoded RGG box. Here, we provide evidence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…One possibility is that in the activated synapse, FMRP is polyubiquitinated and rapidly degraded by the proteasome to relieve the translational inhibition (Hou et al, 2006; Nalavadi et al, 2012). Another possibility is that post-translational modification of FMRP (phosphorylation or methylation) will modulate its affinity for the ribosome (Blackwell and Ceman, 2011; Ceman et al, 2003; Denman, 2002; Dolzhanskaya et al, 2006; Siomi et al, 2002). More studies are needed to understand how the interaction of FMRP with the ribosome is modulated by sequences or structures in the mRNA and by modifications to FMRP.…”
Section: Mechanism Of Translational Repression By Fmrpmentioning
confidence: 99%
“…One possibility is that in the activated synapse, FMRP is polyubiquitinated and rapidly degraded by the proteasome to relieve the translational inhibition (Hou et al, 2006; Nalavadi et al, 2012). Another possibility is that post-translational modification of FMRP (phosphorylation or methylation) will modulate its affinity for the ribosome (Blackwell and Ceman, 2011; Ceman et al, 2003; Denman, 2002; Dolzhanskaya et al, 2006; Siomi et al, 2002). More studies are needed to understand how the interaction of FMRP with the ribosome is modulated by sequences or structures in the mRNA and by modifications to FMRP.…”
Section: Mechanism Of Translational Repression By Fmrpmentioning
confidence: 99%
“…In its unmethylated form, FMRP binds RNAs containing a G‐quadruplex structure (sc1‐like RNA, black). Upon activation, PRMT1 (yellow) methylates FMRP, rendering it unable to bind G‐quadruplex‐containing structures, but is still able to bind other RNAs such as AATYK (green; Blackwell and Ceman, 2011), which participate in neurite outgrowth (Tomomura et al, 2007). PRMT1 is modulated by the cell cycle (Kim et al, 2010), and is required for neurite outgrowth (Miyata et al, 2008).…”
Section: Role Of Arginine Methylation Of Rna‐binding Proteins In Neurmentioning
confidence: 99%
“…Although the sites of methylation for FMRP have been identified (Stetler et al, 2006) and PRMT1 has been identified as a PRMT capable of methylating the protein in cells (Blackwell et al, 2010), additional PRMTs have been shown to methylate FMRP in vitro (Dolzhanskaya et al, 2006) and might also be capable of methylating one or more sites within FMRP in vivo. Methylation of FMRP has been shown to affect RNA association (Blackwell et al, 2010), and the RGG box is required for association with the RNA‐binding protein Yb1/p50 (Blackwell and Ceman, 2011), suggesting that methylation may also affect protein interactions. It is possible that methylation of FMRP affects binding of both RNAs and protein or, alternatively, that only RNA binding is affected and RNA binding is a prerequisite for protein binding (or vice versa).…”
Section: Perspectivementioning
confidence: 99%
“…Notably, binding of FMRP to G-rich RNAs in vitro requires only the RGG motif, which specifically interacts with natural and in vitro selected G-quadruplex-containing RNAs such as a 35-nucleotide sc1 RNA (21,(26)(27)(28)(29). Recent studies showed that G-quadruplexes facilitate mRNA interactions with ribosome-bound FMRP (30), whereas the RGG motif, in addition to mRNA binding, contributes to association with ribosomes and proteins and translational control (14,(31)(32)(33)(34). The RGG motif is well conserved in FMRP of vertebrates but differs significantly from…”
mentioning
confidence: 99%